Design of an e-booklet on pineapple waste management with project-ESD as learning media for students - Suraida, Suraida; Ma'ruf, Reza; Nurhaliza, Nurhaliza; Nuraida, Nining; Syefrinando, Boby; Salahuddin, Salahuddin; Susanti, Try (Indonesian Research Journal in Education |IRJE|, 2026)
This research uses the research and development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The e-booklet product developed has special characteristics because it integrates a project-based learning approach with ESD values, thereby encouraging students to think critically and creatively and to be aware of environmental and sustainability issues. The analysis stage includes needs analysis through surveys and interviews, curriculum analysis, and student characteristics analysis. Design stage with product prototyping. Three experts (1 material expert, 1 media expert, and 1 linguist) carry out the development stage by validating the product. The results of expert validation showed high eligibility rates: 94.5% for linguists, 90% for material experts, and 88% for design experts. Meanwhile, the results of the practicality test received scores of 91% from lecturers and 94.75% from students, both of which are in the very practical category. Thus, this project's ESD e-booklet can serve as a context-based learning resource that supports the implementation of sustainable development-oriented education (ESD) in higher education.